Does COVID-19 stress affect the individual work performance (IWP) of health workers in hospitals during the pandemic? Apakah stres COVID-19 mempengaruhi individual work performance (IWP) pada tenaga kesehatan di rumah sakit selama masa pandemi? - Zamralita; Aurelio Hermawan; Debora Basaria (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Health workers are at the frontline risk of contracting the COVID-19 virus. This study aims to determine the effect of COVID-19 stress on individual work performance in health workers in hospitals during the pandemic. The measuring tool used is the COVID Stress Scale and Individual Work Performance Questionnaire/ This study uses a quantitative descriptive method. The participants in this study were 220 health workers. The results showed that there was an effect of COVID-19 stress on individual work performance in health workers during a pandemic with a significance level (Sig) .000< .05. From the results of coefficient determination (R Square), a contribution is .368 obtained.